ORGANIZATION/ INDIVIDUAL RELATIONS AND RETENTION - Rahmatullah; Abdul Wahab; Alim Syariati; Hamzah Tacong (LPPM STAI Muhammadiyah Probolinggo, 2026)
Organizational success is strongly influenced by the quality of the relationship between individuals and the organization. Harmonious relationships can enhance employee commitment, job satisfaction, loyalty, and retention. This study aims to analyze the relationship between individuals and organizations, the concept of Person-Organization Fit (P-O Fit), the exemplary leadership of the Prophet Muhammad (peace be upon him) in human resource management, and the factors affecting employee retention. The study employs a library research method by reviewing literature related to organizational behavior, human resource management, and Islamic perspectives. The findings reveal that strong relationships between individuals and organizations are formed through psychological contracts and psychological ownership, which contribute to organizational commitment and reduce employee turnover. Furthermore, the concept of Person-Organization Fit helps align individual and organizational values, improving employee performance and organizational effectiveness. From an Islamic perspective, the Prophet Muhammad’s values of shiddiq, amanah, fathanah, and tabligh provide a strong ethical foundation for effective human resource management. In addition, employee retention is influenced by organizational culture, career development opportunities, compensation, job design, and interpersonal relationships within the workplace.